2013
DOI: 10.1161/circresaha.113.279984
|View full text |Cite
|
Sign up to set email alerts
|

Combined Deficiency in Glutathione Peroxidase 4 and Vitamin E Causes Multiorgan Thrombus Formation and Early Death in Mice

Abstract: Rationale: Growing evidence indicates that oxidative stress contributes markedly to endothelial dysfunction. The selenoenzyme glutathione peroxidase 4 (Gpx4) is an intracellular antioxidant enzyme important for the protection of membranes by its unique activity to reduce complex hydroperoxides in membrane bilayers and lipoprotein particles. Yet a role of Gpx4 in endothelial cell function has remained enigmatic. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 40 publications
2
97
0
Order By: Relevance
“…They reported their findings on endothelial-specific conditional Gpx4 floxed mice, a model in which endothelial ferroptosis is induced by tamoxifen administration. 119 Under homeostatic conditions, these mice did not show apparent abnormalities. When these mice were fed vitamin E-depleted chow before endothelial ablation of GPX-4, detachment of endothelium with massive thrombotic microangiopathy and renal failure occurred and subsequently all mice rapidly died of multi-organ failure.…”
Section: Ferroptosis In Renal Diseasesmentioning
confidence: 89%
See 1 more Smart Citation
“…They reported their findings on endothelial-specific conditional Gpx4 floxed mice, a model in which endothelial ferroptosis is induced by tamoxifen administration. 119 Under homeostatic conditions, these mice did not show apparent abnormalities. When these mice were fed vitamin E-depleted chow before endothelial ablation of GPX-4, detachment of endothelium with massive thrombotic microangiopathy and renal failure occurred and subsequently all mice rapidly died of multi-organ failure.…”
Section: Ferroptosis In Renal Diseasesmentioning
confidence: 89%
“…118 It remains unclear if ferroptosis plays a role in endotoxic shock-associated renal failure because the later-generation ferrostatins (or conditional ablation of Gpx4) were not tested in this model. A study by Wortmann et al 119 highlighted that besides RN in tubular epithelial cells, other parenchymal cells also are of importance in renal homeostasis. They reported their findings on endothelial-specific conditional Gpx4 floxed mice, a model in which endothelial ferroptosis is induced by tamoxifen administration.…”
Section: Ferroptosis In Renal Diseasesmentioning
confidence: 99%
“…Thus, vitamin E acts as the compensating ROS scavenger and provides a back-up system for Gpx4 in vivo, as it has recently been suggested in endothelial cells. 33 hemolytic anemia, but rather are characterized by insufficient erythropoiesis. Lipid peroxidation, ROS formation, and induction of necrosis have been linked by several groups [39][40][41][42] to an increase in redox-active iron, the so-called intracellular labile iron pool, and to an increase in lysosomal iron.…”
Section: Gpx4 Prevents Necroptosis In Erythroid Precursors 145mentioning
confidence: 99%
“…33 To examine whether this was also the case during reticulocyte maturation, and to restrict Gpx4 deletion to the hematopoietic system, we performed adoptive transfer experiments using bone marrow derived from Gpx4 F/F or Gpx4 D mice.…”
mentioning
confidence: 99%
“…We have elucidated the roles of GPx4 in photoreceptors [18], retinal pigment epithelium [19], and conjunctival cells [20]. Systemic abrogation of GPx4 leads to lethality on embryonic day 7 [21], and studies have identified drastic disease phenotypes of photoreceptors [18], cerebral neurons [22], vascular endothelium [23], and spermatocytes in conditional knockout mice [24]. …”
Section: Introductionmentioning
confidence: 99%